Study of leadership style with the successfulness of the societies and clubs in UiTM Melaka / Nurul Izati Mansor and Nurul Ain Poniran - Mansor, Nurul Izati; Poniran, Nurul Ain (Faculty of Administrative Science and Policy Studies, 2012)
There is many types of leadership that being practices by the leader. This research focus on how the leadership style being practices by the leader where we narrow down the leader in the societies and club. The involvement of student that guide and lead the flow of the associations. Besides that, there have three types of leadership have been focused here. Either the democratic is the leadership style that more preferable, however in the IPTA or in educational level the practices is differ. The IPTA more practices liaises-faire. There have some reasons that they more prefer these types of leadership. This is because the function of the leader only as the people who have the authority but they are less involved in the activities being held. The laissez-faire is the leader that only gives the instruction and command on the activities will be operate only. The other is under the responsibility of each members of association especially the vice president that have the power to act or represent the president in the absent and not exceed the authority as given. Through this research study we was find out that thee laissez-faire is the most practices leadership style among leader of society in UiTM Melaka. Beside that, there is some leader that comes out with their own reason why they practices this laissez-faire as their leadership practices. This is because the involvement of them in the University level is not too challenge them as a leader and there is no competition from others because they was appoint by their members because of their ability and the academic achievements, on how they interact with others.